2018
DOI: 10.1119/1.5001933
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the use of notebooks in upper-division physics lab courses

Abstract: The use of lab notebooks for scientific documentation is a ubiquitous part of physics research. However, it is common for undergraduate physics laboratory courses not to emphasize the development of documentation skills, despite the fact that such courses are some of the earliest opportunities for students to start engaging in this practice. One potential impediment to the inclusion of explicit documentation training is that it may be unclear to instructors which features of authentic documentation practice ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…[BFY, PhysEng, Small] Another instructor used writing to address goals of the class because "Even though no lab work occurred after remote instruction began, students had to rely on their notebooks and previous data collection to complete required oral presentations and written reports, both considered part of 'lab skills.' "[BFY, PhysEng, Small] This is in line with recommendations from Stanley and Lewandowski [13] for using notebooks in upper-division lab classes in a way that promotes authentic documentation by requiring students to rely on their own (or others') notebooks.…”
Section: Writing In Labssupporting
confidence: 67%
See 1 more Smart Citation
“…[BFY, PhysEng, Small] Another instructor used writing to address goals of the class because "Even though no lab work occurred after remote instruction began, students had to rely on their notebooks and previous data collection to complete required oral presentations and written reports, both considered part of 'lab skills.' "[BFY, PhysEng, Small] This is in line with recommendations from Stanley and Lewandowski [13] for using notebooks in upper-division lab classes in a way that promotes authentic documentation by requiring students to rely on their own (or others') notebooks.…”
Section: Writing In Labssupporting
confidence: 67%
“…For example, courses focusing on the development of communication skills (see Section 6) could still get students to produce written work and provide feedback to them. As, in most situations, students had gathered some data already, this led to an opportunity to highlight the value associated with making good lab notes [13]: "Even though no lab work occurred after remote instruction began, students had to rely on their notebooks and previous data collection to complete required oral presentations and written reports, both considered part of 'lab skills.' (i.e., experimental physics skills)" [BFY, PhysEng, Small].…”
Section: Skillsmentioning
confidence: 99%
“…In Eblen-Zayas' example, the ELNs were graded and carried weight in the students' overall grade in order to emphasize the importance of keeping a lab notebook. Stanley and Lewandowski 26 provide additional recommendations for instruction around lab notebooks including having flexibility around the format and structure of notebook entries, clearly conveying to students that they should attend to context, audience, and purpose in their notebook entries, and designing lab activities such that students have to rely on their own (or others') notebooks.…”
Section: B Writing In Labsmentioning
confidence: 99%
“…Undergraduate physics lab courses are characterized by a variety of learning objectives [1], including developing proficiency with troubleshooting [2], modeling [3], and technical writing [4][5][6][7][8]. National interview studies with instructors have found that some instructors want students to develop sophisticated views about experimental physics, such as the belief that 'nothing works the first time' when conducting experiments [9] or the perception of experimentation as an iterative process [10].…”
Section: Introductionmentioning
confidence: 99%